Risk practices for HIV transmission among adults in the city of General Elizardo Aquino, December 2014 - January 2015. Paraguay - Rios-González, Carlos Miguel (2015)
Objective: Identify unsafe practices for HIV transmission in adults of General Elizardo Aquino city. Material and Methods: Observational, descriptive cross-sectional study with non-probability sampling of consecutive cases on unsafe practices for transmission of HIV in adults in the city of General Elizardo Aquino. Respondents were previously informed about the objectives of the study and those who agreed continued to fill the survey. Data were collected through a mixed type survey containing the variables of interest. Results are expressed in frequency tables and prevalence. Results: sex. 40.24 % (n= 68) had at least once involved alcohol during intercourse and 1.75% (n= 3) had sex with intravenous drug users. 19.77% (n=17) of the females never used a condom during intercourse. From 1-10 people varied the number of sexual partners during the past 3 months (3.29 ± 1.29). Conclusions: The most frequent risk practices are low use of condoms, the large number of sexual partners throughout their lives and for the past three months, also the rapid HIV test is not performed.